An inquiry into the perceptions of leisure-work-family conflict among female Ironman participants. (1st January 2013) - Hambrick, Marion E.; Simmons, Jason M.; Mahoney, Tara Q.
Triathlon is one of the fastest growing niche sports in the USA (USA Triathlon, 2012). Niche sports are often characterised as lifestyle sports (Miloch and Lambrecht, 2006; Puchan, 2005), and can create inter-role conflict as athletes balance their sport participation with the demands of potentially competing roles such as spouse, parent and employee (Greenhaus and Beutell, 1985). This study examined perceptions of inter-role conflict among leisure, work and family roles with niche sport athletes-specifically female Ironman participants. Semi-structured interviews were conducted with 13 women to identify factors influencing their perceptions of inter-role conflict and how they negotiated those factors. The athletes faced obstacles such as financial commitments, time restraints and gender stereotypes, and they used their support systems comprised of family members, friends and colleagues as well as role management strategies to navigate the obstacles. Theoretical and practical findings for employers and niche sport event organisers are discussed.